1990
DOI: 10.1111/j.1399-6576.1990.tb03147.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary clearance of 99mTc‐DTPA during halothane anaesthesia

Abstract: We studied the integrity of the alveolo-capillary barrier during different forms of anaesthesia by measuring the pulmonary clearance of inhaled 99mTc-DTPA. We studied four groups of rabbits. Groups I and II were anaesthetized with nembuthal only and the fractional concentration of inspired oxygen (F1O2) was 0.30 and 1.00, respectively. Groups III and IV were anaesthetized with 1% halothane and F1O2 was 0.30 and 0.99, respectively. 99mTc-DTPA was administered as a fine aerosol and the clearance of the tracer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 18 publications
(17 reference statements)
0
11
0
2
Order By: Relevance
“…The mechanisms whereby halothane induced a decrease in sodium transport protein activity have not been yet elucidated but are not related in vitro to a decrease in intracellular ATP content or to change in cytosolic free calcium. Also, some studies show that halothane increases permeability of alveolar capillary barrier to both water and protein as measured by the pulmonary clearance of 99m TcDTPA in both rabbit (384) and humans (58). Taken together, these observations suggest that halogenated anesthetics may interfere with the clearance of alveolar edema.…”
Section: Anestheticsmentioning
confidence: 99%
“…The mechanisms whereby halothane induced a decrease in sodium transport protein activity have not been yet elucidated but are not related in vitro to a decrease in intracellular ATP content or to change in cytosolic free calcium. Also, some studies show that halothane increases permeability of alveolar capillary barrier to both water and protein as measured by the pulmonary clearance of 99m TcDTPA in both rabbit (384) and humans (58). Taken together, these observations suggest that halogenated anesthetics may interfere with the clearance of alveolar edema.…”
Section: Anestheticsmentioning
confidence: 99%
“…The tmax for S-salbutamol, as well as for R-salbutamol, was found to be about twice as high after endotracheal administration as after an inhaled administration. In contrast to the findings during general anaesthesia, a tmax was already recorded within a few minutes after a canister of salbutamol metered-dose inhaler (MDI) was actuated via an intratracheal catheter in rabbits anaesthetized by halothane and ventilated with 100% O 2 [17]. It is not known whether the latter findings were influenced by dysfunction of surfactant, presumably depleted by halothane in combination with 100% O 2 , or whether this was a combined effect of induced epithelial damage [18].…”
Section: Discussionmentioning
confidence: 93%
“…(18) and systemic diseases such as Behçet's disease (19) have caused increased lung clearance of Tc-99m DTPA. Some researchers have found significantly rapid pulmonary clearance of Tc-99m DTPA in rabbits under general anesthesia with high oxygen concentrations (79%) (20,21). Therefore, the more rapid pulmonary clearance of Tc-99m DTPA in patients who received desflurane and sevoflurane could be due to the effects of inhaler anesthetics rather than oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers found no significant change in alveolar epithelial permeability before surgery and after surgery (22). Wollmer et al (21) showed that halothane, in combination with high oxygen concentrations, increases the permeability of the alveolarcapillary barrier. However, in our study, during the maintenance of anesthesia, all patients were mechanically ventilated with low oxygen (40% oxygen).…”
Section: Discussionmentioning
confidence: 99%